Assessment of metal contents in commercially available Ethiopian red pepper - Tefera, M. (2023)
The concentrations of major (Na, K, Ca) and trace (Fe, Co, Cu, Mn, Zn, Ni, Cr, Cd and Pb) metals were determined in Ethiopian red pepper samples collected from Alaba, Mareko and Addis Ababa open market (Merkato) using flame atomic absorption spectrometry after wet digestion. The metal concentrations in the samples were found to be K 2378–2486, Ca 161–222, Na 75.0–93.0, Fe 99.5–157, Cr 27.5–78.6, Zn 20.8–58.4, Mn 9.72–18.9, Ni 2.71–6.68, Cu 2.12–3.71, Co 1.02–2.24 and Cd 0.18–0.23 in μg g–1, respectively. Pb was not detected in any of the pepper samples. The levels of metals K, Na and Ca in the red pepper samples from Alaba were found to be higher than those from Mareko and Addis Ababa open market. The levels of Co, Cu, Ni, Zn and Cd were found to be higher in samples from Mareko than in samples from Alaba and Addis Ababa open market pepper. The levels of Cr and Mn were higher in Addis Ababa open market pepper. The concentrations of metals in Ethiopian pepper are comparable to values reported in literature from different parts of the world. The trace metals levels in all the three samples were found to be lower than the World Health Organization (WHO)allowed limit. However, levels of Cd and Cr were above the WHO limit. The concentrations of metals in Ethiopian red pepper are comparable to values reported in the other spices in the literature. Furthermore, to correlate metal concentrations among each other metal levels in the red pepper using Pearson’s correlation coefficient (r) was determined and except for few metals, most relationships showed either strong positive or negative linear relationships. From this relationship it can be understood that the presence of one metal in the plant influence the presence of the other.